2021
DOI: 10.1093/toxsci/kfab143
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Toxicogenomics of Glyphosate and Roundup Herbicides by Mammalian Stem Cell-Based Genotoxicity Assays and Molecular Profiling in Sprague-Dawley Rats

Abstract: Whether glyphosate-based herbicides (GBHs) are more potent than glyphosate alone at activating cellular mechanisms, which drive carcinogenesis remains controversial. As GBHs are more cytotoxic that glyphosate, we reasoned they may also be more capable of activating carcinogenic pathways. We tested this hypothesis by comparing the effects of glyphosate with Roundup GBHs both in vitro and in vivo. First, glyphosate was compared with representative GBHs namely MON 52276 (EU), MON 76473 (UK) and MON 76207 (USA) us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 69 publications
2
21
0
Order By: Relevance
“…In addition, upregulation of genes involved in ribonucleoprotein complex assembly and ribonucleoprotein complex subunit organization in both Hep1 and Hep2 suggests potential DNA damage of GLY (Fig. 3 E), which has been reported previously [ 23 ]. Overall, GLY may cause oxidative stress, abnormal lipid metabolism, inflammatory response, and DNA damage, suggesting GLY-induced dysregulation of hepatocytes.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…In addition, upregulation of genes involved in ribonucleoprotein complex assembly and ribonucleoprotein complex subunit organization in both Hep1 and Hep2 suggests potential DNA damage of GLY (Fig. 3 E), which has been reported previously [ 23 ]. Overall, GLY may cause oxidative stress, abnormal lipid metabolism, inflammatory response, and DNA damage, suggesting GLY-induced dysregulation of hepatocytes.…”
Section: Resultssupporting
confidence: 83%
“…Mesnage et al. observed activated oxidative stress (reflected by Srxn1 and Blvrb) in mammalian stem cell-based ToxTracker system by glyphosate-based herbicides but not glyphosate itself [ 23 ], In our study, the expression level of Srxn1 and Blvrb (Fig. 3 G and Additional file 2 : Table S9) was improved after GLY exposure.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…Supporting this evidence, more recently, perinatal G exposure in mice was associated with aberrant expression of lncRNAs, highlighting a link with impaired neuronal development ( 55 ). Also changes in miRNA profile in female rat liver were assessed following G and G-based herbicide treatment, and interestingly these miRNAs were associated with carcinogenesis, like miR-17 and miR-22 ( 56 ). Furthermore, an in vitro study performed on carp lymphocytes shown that G-induced lymphocyte apoptosis was mediated by the regulation of miR-203 and PI3K/AKT pathway ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Polyethoxylated tallowamine (POE-15) is a main surfactant in herbicide Roundup Classic, the chemical acts as a tackifier by helping its adsorption on plant surfaces and uptake by plants, and it also facilitates its uptake to cells though disturbing membrane (cell wall) processes. Increased toxicity of POE-15-formulated GBHs compared to glyphosate has been documented in the scientific literature [47] , [48] , and POE-15 and other co-formulants alone also exerts numerous side effects, for example genotoxicity, cytotoxicity [28] , [47] , [49] , [50] , [51] , [52] , [53] . GBHs containing POE-15 were banned in the EU in 2016 [54] , and the ban was extended to polypropoxylated tallowamines and a number of other co-formulants in 2021 [55] .…”
Section: Introductionmentioning
confidence: 99%